Ansiedad, depresión y uso excesivo de Internet en la calidad de sueño de estudiantes de medicina veterinaria y zootecnia - Chui B., Heber (2023)
The study aimed to examine the excessive use of the Internet in the mental health of students of Veterinary Medicine and Zootechnics at the National University of the Alti-plano, Puno, Peru. The study was descriptive, explanatory and cross-sectional, carried out with 226 students (152 men and 74 women) from I to X cycle, aged 23.4 ± 5.5 years. Mental health was related to anxiety, depression and the sleep quality index. Internet use was quantified through a survey, exploring the time (h/day) of use during the last 30 days; anxiety and depression were determined through the Hamilton Rating Scale (HARS and HDRS), with internal consistency, α = 0.93 and 0.89, respectively; and the sleep quality index using the Pittsburgh questionnaire (α=0.87). The results indicate that depression (β= 0.292; p<0.001), anxiety (β = 0.229; p<0.001) and excessive use of the Internet (β = 0.178; p<0.01) are the aspects that contributed the most (p <0.001) in the students’ sleep quality index.